The effectiveness of shared clinical teaching in nursing - Karen F. Phillips; Lizy Mathew; Nadine Aktan; Priyadharshiny Sandanapitchai (Elsevier, 2019)
Aim: Clinical learning is a critical component of a nursing curriculum. Student satisfaction in clinical environment is crucial to foster a positive learning experience. Faculty shortages have made clinical teaching more challenging; as such, alternate models of clinical teaching must be explored by nursing programs. The purpose of this study was to measure the perception of student satisfaction in regard to the effectiveness of shared clinical teaching in nursing. Methods: Utilizing Chan's Clinical Learning Environment Inventory (CLEI), this quantitative comparative study examined nursing students' preferred and actual clinical learning environment. The CLEI contains 42 questions in six subscales: Individualization, Innovation, Involvement, Personalization, Task Orientation, and Satisfaction in both the actual and preferred clinical learning environment. The sample consisted of 202 nursing students in two groups: the first group had 91 students who experienced shared clinical teaching with two faculty, whereas the second group had 111 students who experienced the traditional, single faculty model. The results were analyzed using independent sample T-tests. Results: The preferred learning environment was rated highest in all six subscales. Scores of the Satisfaction subscale and the Innovation subscale for Actual Learning Environment, and the score of the Innovation subscale for Preferred Learning Environment of students experiencing shared clinical teaching with two faculty were higher than the scores of students experiencing traditional, single faculty model, with statistically significance (P＜0.05). Conclusion: The results indicated students preferred the shared clinical teaching model with two faculty over the single faculty model. Nursing programs can utilize this model and apply these results to develop and maintain quality clinical teaching. Keywords: Clinical Clerkship, Clinical learning environment, Faculty shortage, Nursing education, Students, Nursing, Questionnaires